Perspective of Small Medium Enterprises in West Nusa Tenggara on export plans - Riduan Mas'ud; Muhammad Azizurrohman; Khairul Hamim; Baiq Elbadriati; Supiandi Supiandi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2022)
Purpose — The purpose of this study is to investigate how Small Medium Enterprises (SMEs) react to their plans to engage in export activities, particularly in the province of West Nusa Tenggara (NTB).Research method — The method used in this research is descriptive quantitative by distributing questionnaires to respondents containing multiple choice and open-ended questions.Result — This study found that the majority of SMEs have been export-oriented. They want to export for a variety of reasons, including expansion of their business network, international market demand, increased company revenues, and availability of suitable raw materials. Lack of extensive overseas markets/networks, lack of understanding of export procedures, and lack of adequate Human Resources seem to be one of the reasons given by SMEs who say NO or do not want to carry out export activities (HR).Significance/contribution/recommendation — In terms of the issues covered, this study differs from others. The majority of research focuses solely on the impact of SMEs and their export prospects. Meanwhile, the focus of this research is on SMEs' responses when it comes to organizing their product export efforts.